Interfacing industrial R&A equipment using Matlab. - Pires, J.N (IEEE Robotics and automation magazine)
We present a toolbox that enables access to real robotics and automation (R&A) equipment from the MATLAB shell. If used in conjunction with a robotics toolbox, it will extend significantly their application, i.e., besides robotic simulation and data analysis, the user can interact online with the equipment he or she is using. This article briefly presents the software architecture adopted and how it was used to generate the MATLAB MEX files presented. It then exemplifies application to two types of equipment, complemented with a generic manipulation example using a robotic gripper. The utilization of this tool with force control experiments is also briefly explored